Development and Characterization of Poly-e-Caprolactone Based Microspheres-A Sustained Drug Delivery System for Treating Rheumatoid Arthritis - Shanmugam1, Saranya; Anju2, T.; Veluswamy1, iyarasan; Ankita Betala2, S.; Priya Singh2, Charu; Singh2, Shivani (Asian Journal of Chemistry, 2013)
Rheumatoid arthritis is an autoimmune disorder with a characteristic feature of chronic inflammation of the joints. This disease can also cause inflammation and injury in other organs in the body, but principally attacks flexible (synovial) joints. The commonly prescribed medication for this disorder includes steroids which can cause side effects like bruising, cataracts, muscle weakness, osteoporosis, infections and blocking of other immune response. Hence a polymeric drug carrier has been designed to provide a stealth characteristic to the delivery system and prolonged blood circulation. In the present study we have developed two different poly-e-caprolactone based delivery systems with dexamethasone and prednisolone. Efficient encapsulation of dexamethasone and prednisolone in poly-e-caprolactone microspheres were carried out using oil-water single emulsion solvent evaporation method. The microspheres formed were characterized for encapsulation efficiency, particle size analysis, morphological characteristics and the drug release profiles. The particle size distribution of the poly-e-caprolactone spheres was narrow in the range 5-20 μm. The characterization processes carried out by SEM, particle size analyzer, AFM and FTIR showed efficient encapsulation and the in vitro release studies highlighted them as potential sustained drug delivery systems. The specificity of the system might be granted by conjugating the polymeric microcarrier with the respective ligand so that it functions effectively.